Solid-state battery and preparation method thereof, battery device, power consumption device, and energy storage device

CN122677500BActive Publication Date: 2026-10-27ZHEJIANG JINKO ENERGY STORAGE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611167209.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

[0003]固态电池中,电极和固态电解液之间是刚性接触,无法像液态电解质那样充分浸润电极,使得固态电池存在循环寿命短、倍率性能差以及易短路等一系列的问题,导致固态电池的电化学性能劣化

Benefits of technology

本申请Li-Al-F-O玻璃相在固态电池中可以以两种不同的形式存在:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122677500B_ABST
    Figure CN122677500B_ABST
Patent Text Reader

Abstract

The application provides a solid-state battery and a preparation method thereof, a battery device, a power utilization device and an energy storage device. The solid-state battery comprises a positive electrode, a negative electrode and an electrolyte film, the electrolyte film is located between the positive electrode and the negative electrode, the positive electrode comprises a composite positive electrode material layer, the composite positive electrode material layer comprises a positive electrode active material and an ion conductor; the positive electrode further comprises a coating layer located on the surface of the positive electrode active material, the coating layer comprises a Li-Al-F-O glass phase; an oxyacid salt containing fluorine elements and lithium elements is further arranged between the composite positive electrode material layer and the electrolyte film. The solid-state battery can improve the interface stability between the positive electrode and the electrolyte film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid-state battery technology, and in particular to solid-state batteries and their preparation methods, battery devices, power devices, and energy storage devices. Background Technology

[0002] Solid-state batteries are a type of battery technology that uses solid electrodes and solid electrolytes. They eliminate the flammable and volatile liquid or gel electrolytes and separators found in traditional batteries. Solid-state batteries have advantages such as good safety, high energy density, and long cycle life, and are expected to be widely used in electric vehicles and consumer electronics.

[0003] In solid-state batteries, the electrodes and solid electrolytes are in rigid contact, which prevents the electrodes from being fully wetted like liquid electrolytes. This results in a series of problems for solid-state batteries, such as short cycle life, poor rate performance, and susceptibility to short circuits, leading to a deterioration in the electrochemical performance of solid-state batteries.

[0004] Therefore, how to effectively improve the electrochemical performance of solid-state batteries remains one of the technical problems that need to be solved. Summary of the Invention

[0005] This application provides a solid-state battery and its preparation method, battery device, power consumption device and energy storage device. The solid-state battery of this application can improve the interfacial stability between the positive electrode and the electrolyte membrane.

[0006] In a first aspect, embodiments of this application provide a solid-state battery, the solid-state battery including a positive electrode, a negative electrode and an electrolyte membrane, the electrolyte membrane being located between the positive electrode and the negative electrode, the positive electrode including a composite positive electrode material layer, the composite positive electrode material layer including a positive electrode active material and an ion conductor; The positive electrode also includes a coating layer located on the surface of the positive electrode active material, the coating layer comprising a Li-Al-FO glass phase; An oxyacid salt containing fluorine and lithium is also disposed between the composite cathode material layer and the electrolyte membrane.

[0007] Secondly, embodiments of this application provide a solid-state battery, the solid-state battery including a positive electrode, a negative electrode and an electrolyte membrane, the electrolyte membrane being located between the positive electrode and the negative electrode, the positive electrode including a composite positive electrode material layer, the composite positive electrode material layer including a positive electrode active material and an ion conductor; The positive electrode further includes an interface layer located between the composite positive electrode material layer and the electrolyte membrane. The interface layer includes a first interface layer and a second interface layer. The second interface layer is located between the first interface layer and the electrolyte membrane. The first interface layer includes a Li-Al-FO glass phase, and the second interface layer includes an oxyacid salt containing fluorine and lithium.

[0008] Thirdly, embodiments of this application provide a method for preparing a solid-state battery, comprising the following steps: A positive electrode active material was obtained, and the positive electrode active material was coated with a Li-Al-FO glass phase precursor solution to obtain a first precursor. An ion conductor is obtained by mixing the first precursor and the ion conductor and then performing a molding process to obtain a composite cathode material layer. A solution containing oxyacid salts is coated onto the surface of the composite cathode material layer and then dried to form a cathode; or An electrolyte membrane body is obtained by coating a solution comprising an oxoacid salt onto the surface of the electrolyte membrane body and drying it to form an electrolyte membrane; wherein the oxoacid salt contains fluorine and lithium. A negative electrode is obtained, and the positive electrode, electrolyte membrane and negative electrode are stacked to form an electrode assembly, which is then formed to obtain a solid-state battery.

[0009] Fourthly, embodiments of this application provide a method for preparing a solid-state battery, comprising the following steps: A positive electrode active material and an ion conductor are obtained. The positive electrode active material and the ion conductor are mixed and then subjected to molding treatment to obtain a composite positive electrode material layer. The Li-Al-FO glass phase precursor solution is coated on the surface of the composite cathode material and dried to form the first interface layer. A solution comprising an oxyacid salt is coated onto the surface of the first interface layer, and after drying, a second interface layer is formed to obtain a second precursor; wherein the oxyacid salt contains fluorine and lithium. An electrolyte membrane and a negative electrode are obtained. The second precursor, the electrolyte membrane, and the negative electrode are stacked to form an electrode assembly, which is then formed to obtain a solid-state battery.

[0010] Fifthly, embodiments of this application provide a battery device, including a solid-state battery prepared by the method described in the first aspect, the second aspect, the third aspect, or the fourth aspect, and the battery device includes one or more of a battery module, a battery pack, and an energy storage battery.

[0011] Sixthly, embodiments of this application provide an electrical device including a battery device as described in the fifth aspect, the battery device being used to obtain electrical energy.

[0012] In a seventh aspect, embodiments of this application provide an energy storage device, including a battery device as described in the fifth aspect, the battery device being used to store electrical energy.

[0013] The beneficial effects of this application are as follows: In this application, the Li-Al-FO glass phase can exist in two different forms in solid-state batteries: The Li-Al-FO glass phase, as a coating layer for the positive electrode active material, can directly protect the positive electrode active material particles and effectively inhibit the oxidation, decomposition, and dissolution of the positive electrode active material under high voltage. At the same time, each positive electrode active material particle is independently protected, avoiding the risk of internal particles being exposed to the electrolyte.

[0014] The Li-Al-FO glass phase, serving as the interface layer between the composite cathode material layer and the electrolyte membrane, directly targets the interface between the cathode and the electrolyte membrane. It can effectively block the migration of halide ions from the electrolyte membrane to the cathode, while improving the physical contact between the composite cathode material layer and the electrolyte membrane, reducing interfacial voids and contact resistance. Attached Figure Description

[0015] Figure 1 A schematic diagram of the structure of the positive electrode provided in an embodiment of this application; Figure 2 This is a schematic diagram of a solid-state battery provided in an embodiment of this application; Figure 3 This is a schematic diagram of a solid-state battery fabrication process provided in an embodiment of this application; Figure 4 This is a schematic diagram of another fabrication process for a solid-state battery provided in an embodiment of this application.

[0016] In the attached image: 100-Solid-state battery; 1-Positive electrode; 11-Positive electrode active material; 12-Connecting layer; 13-Coating layer; 2-Electrolyte membrane; 3- Negative electrode; 4-First interface layer; 5-Second Interface Layer. Detailed Implementation

[0017] In this embodiment of the application, unless otherwise stated, the character " / " indicates that the preceding and following objects are in an OR relationship. For example, A / B can represent A or B. "AND / OR" describes the relationship between the associated objects, indicating that three relationships can exist. For example, A AND / OR B can represent: A existing alone, A and B existing simultaneously, and B existing alone.

[0018] It should be noted that the terms "first" and "second" used in the embodiments of this application are used only for distinguishing descriptive purposes and should not be construed as indicating or implying relative importance or implicitly indicating the number of technical features indicated, nor should they be construed as indicating or implying order.

[0019] In the embodiments of this application, "at least one" means one or more, and "more than one" means two or more. Furthermore, "at least one of the following" or similar expressions refer to any combination of these items, which may include any combination of a single item or a plurality of items. For example, at least one of A, B, or C can represent: A, B, C, A and B, A and C, B and C, or A, B, and C. Each of A, B, and C can be an element itself or a set containing one or more elements.

[0020] In this application, terms such as "exemplary," "in some embodiments," and "in another embodiment" are used to indicate that something is an example, illustration, or description. Any embodiment or design described as "exemplary" in this application should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the term "exemplary" is intended to present the concept in a concrete manner.

[0021] In the embodiments of this application, the term "equal to" can be used in conjunction with "greater than" to apply to technical solutions employing the condition of "greater than", and can also be used in conjunction with "less than" to apply to technical solutions employing the condition of "less than". It should be noted that when "equal to" is used with "greater than", it cannot be used with "less than"; and when "equal to" is used with "less than", it cannot be used with "greater than".

[0022] With the increasing penetration of intermittent renewable energy sources such as wind and solar power into the power grid, long-duration energy storage technology has become crucial for ensuring grid stability and enabling energy regulation across time periods. Storage durations of 4 to 8 hours or even longer can effectively achieve energy regulation across time periods (such as shifting midday photovoltaic power generation to nighttime peak electricity consumption), which is of great significance for ensuring grid security and improving energy efficiency.

[0023] As the basic building block of energy storage systems, energy storage cells can convert electrical energy into chemical energy and vice versa, enabling the storage and release of energy. In the field of electrochemical cells, although traditional lithium-ion batteries have high energy density and flexible deployment, their inherent liquid organic electrolytes pose serious safety hazards (such as flammability and explosion). Moreover, under long-term charge-discharge conditions, liquid electrolyte batteries exhibit active interfacial side reactions, which exacerbate performance degradation, making it difficult to fully meet the stringent requirements of long-term energy storage for ultra-long lifespan, absolute safety, and extreme economy.

[0024] Solid-state batteries are a type of battery that uses solid electrodes and solid electrolytes. Because solid-state batteries contain solid electrolytes, the contact between the solid electrolyte and the positive and negative electrodes is a solid-solid interface, unlike the solid-liquid contact of traditional liquid batteries. Solid-state batteries have unique advantages in long-term energy storage systems. They do not use flammable and explosive liquid electrolytes, fundamentally eliminating the main risks of fire and explosion. Furthermore, under the typical operating condition of 8 hours of long-term energy storage, the battery system may remain in a fully charged or highly charged state for extended periods. Solid-state batteries possess excellent thermal stability and a wider operating temperature range, effectively eliminating the risks of combustion and explosion caused by electrolyte leakage, volatilization, or thermal runaway. This significantly improves the safety of large-scale energy storage power station operations and reduces the complexity and cost of safety protection systems.

[0025] Despite the high safety and high energy density potential of solid-state batteries, they still face significant challenges on the road to large-scale energy storage applications. One major challenge is the solid-solid interface between the solid electrolyte and the positive and negative electrodes. This interface has high impedance, which greatly affects battery performance.

[0026] In view of this, this application provides a solid-state battery, which includes a positive electrode, a negative electrode and an electrolyte membrane, with the electrolyte membrane located between the positive electrode and the negative electrode. The positive electrode includes a composite positive electrode material layer, which includes a positive electrode active material and an ion conductor. The positive electrode also includes a coating layer located on the surface of the positive electrode active material, the coating layer including a Li-Al-FO glass phase; An oxyacid salt containing fluorine and lithium is also provided between the composite cathode material layer and the electrolyte membrane.

[0027] In the above-described scheme, the solid-state battery of this application includes a coating layer on the surface of the positive electrode active material. This coating layer comprises a Li-Al-FO glass phase. Unlike crystalline materials, the Li-Al-FO glass phase of this application can continuously and uniformly cover the surface of the positive electrode active material, which helps reduce grain boundaries and defects on the surface of the positive electrode active material and improves the interfacial stability of the positive electrode active material. Furthermore, the Li-Al-FO glass phase has a certain ion conductivity, which can improve lithium-ion transport efficiency. This application also includes an oxyacid salt between the composite positive electrode material layer and the electrolyte membrane. The oxyacid salt contains fluorine and lithium elements. During the charge and discharge process of the solid-state battery, compared to the Li-Al-FO glass phase, the aforementioned oxyacid salt will preferentially decompose. The in-situ decomposition of the oxyacid salt forms LiF and oxygen-containing fluorides, which can fill the pinholes and cracks in the Li-Al-FO glass phase, further improving the interfacial stability of the positive electrode active material. The Li-Al-FO glass phase and the oxyacid salt containing fluorine and lithium elements in this application can form a dual fluorine source between the cathode and the electrolyte membrane, achieving a synergistic effect of static protection and dynamic repair, and significantly improving the long-term stability of the cathode and electrolyte membrane interface.

[0028] In some embodiments, the thickness of the coating layer is 5 nm to 50 nm, specifically 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or any value within the range of any two of the above values. The coating layer of this application maintains a continuous and uniform coverage of the positive electrode active material under ultra-thin conditions. If the thickness of the coating layer is less than 5 nm, the continuity of the coating layer decreases, making it prone to defects such as pinholes and cracks, which can easily lead to direct contact between the electrolyte and the positive electrode active material. If the thickness of the coating layer is greater than 50 nm, the excessive thickness of the coating layer leads to a significant increase in interfacial impedance, affecting the lithium-ion transport efficiency. Optionally, the thickness of the coating layer is 5 nm to 10 nm.

[0029] In some embodiments, a connecting layer is provided between the positive electrode active material and the coating layer, which can improve the adhesion between the positive electrode active material and the coating layer. Figure 1 This is a schematic diagram of one possible structure of the positive electrode of this application, such as... Figure 1 As shown, only a structural schematic diagram of a single positive electrode active material particle is shown. A connecting layer 12 and a coating layer 13 are provided on the surface of the positive electrode active material 11. Both the connecting layer 12 and the coating layer 13 are coated on the surface of the positive electrode active material 11, and the connecting layer 12 is located between the positive electrode active material 11 and the coating layer 13.

[0030] In some embodiments, the bonding layer includes at least one of LiNbO3, Li3PO4, Al2O3, TiO2, and La2O3.

[0031] In some implementations, the thickness of the interconnect layer is 1nm to 3nm, specifically 1nm, 1.2nm, 1.5nm, 2nm, 2.2nm, 2.5nm, 2.8nm, 3nm, or any value within the range of any two of the above values.

[0032] In some embodiments, the solid-state battery includes a positive electrode, a negative electrode, and an electrolyte membrane, with the electrolyte membrane located between the positive and negative electrodes. The positive electrode includes a composite positive electrode material layer, which includes a positive electrode active material and an ion conductor. The positive electrode also includes an interface layer located between the composite positive electrode material layer and the electrolyte membrane. The interface layer includes a first interface layer and a second interface layer. The second interface layer is located between the first interface layer and the electrolyte membrane. The first interface layer includes a Li-Al-FO glass phase, and the second interface layer includes an oxyacid salt containing fluorine and lithium elements.

[0033] In the above-described scheme, the solid-state battery of this application has an interface layer between the composite cathode material layer and the electrolyte membrane: a first interface layer and a second interface layer. The first interface layer includes a Li-Al-FO glass phase. Unlike crystalline phases, the Li-Al-FO glass phase of this application can continuously and uniformly cover the surface of the cathode active material, which is beneficial to reducing grain boundaries and defects on the surface of the cathode active material and improving the interface stability of the cathode active material. Moreover, the Li-Al-FO glass phase has a certain ion conductivity, which is beneficial to improving lithium-ion transport efficiency. The second interface layer includes oxyacid salts containing fluorine and lithium. During the charge and discharge process of the solid-state battery, compared with the Li-Al-FO glass phase, the oxyacid salts containing fluorine and lithium will preferentially decompose and decompose in situ to form LiF and oxygen-containing fluorides, which can fill the pinholes and cracks of the Li-Al-FO glass phase and further improve the interface stability of the cathode active material. The Li-Al-FO glass phase and the oxyacid salt containing fluorine and lithium elements in this application can form a dual fluorine source between the cathode and the electrolyte membrane, achieving a synergistic effect of static protection and dynamic repair, and significantly improving the long-term stability of the cathode and electrolyte membrane interface.

[0034] Figure 2 This is a schematic diagram of the structure of a solid-state battery provided in an embodiment of this application, such as... Figure 2 As shown, the solid-state battery 100 includes a positive electrode 1, an electrolyte membrane 2 and a negative electrode 3. A first interface layer 4 and a second interface layer 5 are provided between the positive electrode 1 and the electrolyte membrane 2. The first interface layer 4 is located between the positive electrode 1 and the second interface layer 5.

[0035] In some implementations, continue as Figure 2As shown, the first interface layer 4 is not only disposed between the positive electrode 1 and the electrolyte membrane 2, but also disposed on the surface of the side of the positive electrode 1 facing away from the electrolyte membrane 2. Correspondingly, the second interface layer 5 is not only disposed between the first interface layer 4 and the electrolyte membrane 2, but also disposed on the surface of the side of the positive electrode 1 facing away from the electrolyte membrane 2, that is, the first interface layer 4 and the second interface layer 5 are symmetrically disposed on two opposite sides of the positive electrode 1.

[0036] In some embodiments, the thickness of the first interface layer 4 is 5 nm to 50 nm, specifically may be 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or any value within the range formed by any two of the above values. The first interface layer 4 of the present application maintains continuous and uniform coverage of the positive electrode active material under ultra-thin conditions. If the thickness of the first interface layer 4 is less than 5 nm, the continuity of the first interface layer decreases, defects such as pinholes and cracks are prone to occur, which easily causes the electrolyte to directly contact the positive electrode active material. If the thickness of the first interface layer 4 is greater than 50 nm, the excessively thick first interface layer leads to a significant increase in interface impedance, which affects the transmission efficiency of lithium ions. Optionally, the thickness of the first interface layer is 5 nm to 10 nm.

[0037] In some embodiments, the positive electrode active material includes lithium nickel manganese oxide and derivatives thereof, and the chemical formula of lithium nickel manganese oxide is LiNi 0.5 Mn 1.5 O4, which has a spinel crystal structure. The lithium nickel manganese oxide derivatives include but are not limited to: doped lithium nickel manganese oxide obtained by aliovalent ion doping modification, the doping element is selected from at least one of Mg, Ca, Ti, V, Cr, Fe, Co, Cu, Zn, Y, Zr, Nb, Mo, Ru, Al and Ga, and its chemical formula can be expressed as LiNi 0.5-a Mn 1.5-a M 2a O4, where 0<a≤0.1, and M is the doping element. The lithium nickel manganese oxide derivatives also include lithium nickel manganese oxide-based solid solution materials in which part of nickel and / or manganese is replaced by different transition metal elements, such as lithium nickel cobalt manganese oxide materials. As the positive electrode active material, lithium nickel manganese oxide and its derivatives have a high voltage platform, high theoretical capacity, no cobalt, and excellent rate performance, which are beneficial to the preparation of solid-state batteries with high energy density.

[0038] In some embodiments, the electrolyte membrane includes a first halide, and the general chemical formula of the first halide is Li3MCl6, where M includes at least one of Y, In, Sc, Er and Yb. The above first halide, as an electrolyte, has high ionic conductivity, good mechanical ductility and a wide electrochemical window.

[0039] In some embodiments, the ion conductor includes a second halide with the general chemical formula Li3MCl6, where M includes at least one of Y, In, Sc, Er, and Yb. It should be noted that in this application, the positive electrode active material and the ion conductor together form a composite positive electrode material layer. The ion conductor can provide a lithium-ion conduction path within the positive electrode, ensuring good ion contact between the positive electrode active material particles and between the positive electrode active material and the electrolyte membrane.

[0040] In solid-state battery systems, at a working voltage of 4.7V, a series of side reactions occur on the surface of lithium nickel manganese oxide and its derivatives, including Mn dissolution, oxygen release, and electrolyte oxidation. These reactions become more complex when in contact with halide electrolyte membranes: on the one hand, the high oxidizability of the surface of lithium nickel manganese oxide and its derivatives attacks halides, potentially forming high-resistivity products such as oxyhalides; on the other hand, halide ions may migrate towards the positive electrode and participate in side reactions, further deteriorating the interface. The Li-Al-FO glass phase and oxyacid salts containing fluorine and lithium elements in this application can form a dual fluorine source between the positive electrode and the electrolyte membrane, achieving a synergistic effect of static protection and dynamic repair, significantly improving the long-term stability of the interface between the positive electrode and the electrolyte membrane.

[0041] In this application, the Li-Al-FO glass phase can exist in two different forms in solid-state batteries: The Li-Al-FO glass phase, as a coating layer for the positive electrode active material, can directly protect the positive electrode active material particles and effectively inhibit the oxidation, decomposition, and dissolution of the positive electrode active material under high voltage. At the same time, each positive electrode active material particle is independently protected, avoiding the risk of internal particles being exposed to the electrolyte.

[0042] The Li-Al-FO glass phase, serving as the interface layer between the composite cathode material layer and the electrolyte membrane, directly targets the interface between the cathode and the electrolyte membrane. It can effectively block the migration of halide ions from the electrolyte membrane to the cathode, while improving the physical contact between the composite cathode material layer and the electrolyte membrane, reducing interfacial voids and contact resistance.

[0043] In some embodiments, the general chemical formula of the Li-Al-FO glass phase is LiAlF. 4-a O a , 0 < a ≤ 0.3, where a can be any value within the range of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, or any two of the above values.

[0044] The presence of an appropriate amount of oxygen can optimize the lithium-ion transport channel and significantly improve ion conductivity. At the same time, the introduction of oxygen atoms can precisely regulate the thermodynamic stability of the material, enabling it to form a stable glass phase under mild annealing conditions of 250°C±10°C.

[0045] In some implementations, the Li-Al-FO glass phase exhibits electrochemical stability within an operating window of 4.8V to 5.0V.

[0046] In some embodiments, the electronic conductivity of the Li-Al-FO glass phase is less than or equal to 10. -12 S / cm, specifically 10 -12 S / cm, 5 10 -12 S / cm, 10 -13 S / cm, 5 10 -13 S / cm, 10 -14 S / cm, 5 10 -14 S / cm, 10 -15 S / cm or any value within the range of any two of the above values. The Li-Al-FO glass phase of this application has low electronic conductivity, which can effectively block electron leakage.

[0047] In some embodiments, the ionic conductivity of the Li-Al-FO glass phase at room temperature is 10. -7 S / cm~10 -6 S / cm, specifically 10 -7 S / cm, 2 10 -7 S / cm, 3 10 -7 S / cm, 4 10 -7 S / cm, 5 10 -7 S / cm, 6 10 -7 S / cm, 7 10 -7 S / cm, 8 10 -7 S / cm, 9 10 -7 S / cm, 10 -6 S / cm or any value within the range of any two of the above values. The Li-Al-FO glass phase of this application exhibits excellent ionic conductivity.

[0048] It should be noted that room temperature conditions refer to an environment with a temperature of 25±0.5℃.

[0049] In some embodiments, the oxyacid salt includes at least one of lithium difluorophosphate and lithium difluorooxalate borate. Lithium difluorophosphate (LiPO2F2) decomposes at high potentials, expected to generate LiF and a POF-containing glassy material. Lithium difluorooxalate borate (LiC2BF2O4) decomposes at high potentials, expected to generate LiF and a BOF-containing glassy material, which can not only fill the pinholes and cracks in the Li-Al-FO glass phase, but also enhance the mechanical integrity of the cathode-electrolyte interface phase.

[0050] The mechanism of preferential decomposition of oxyacid salts is explained in detail below using lithium difluorophosphate as an example. Local electric field concentration easily occurs in the interface defect region (such as pinholes and cracks) between the positive electrode and the electrolyte membrane, significantly reducing the activation energy of lithium difluorophosphate's oxidative decomposition, allowing selective reactions to occur at the defect site during the pre-activation stage at 4.6V~4.8V. Secondly, the defect region contains a large number of structural active sites (Mn generated on the surface of the positive electrode active material due to high-voltage oxidation). 3+ Reduced states, oxygen vacancies, and dangling bonds, among other sites, accelerate the breaking of the PF bonds in lithium difluorophosphate through strong chemisorption. Simultaneously, the trace amounts of Cl produced by the decomposition of the first halide electrolyte membrane (Li3MCl6) at high potential... - Y 3+ Active species accumulate at defects and undergo catalytic reactions with lithium difluorophosphate, further lowering the reaction energy barrier. During the reaction, the initial decomposition product LiF provides electronic insulation, chemical stability, and interfacial densification, while the POF-containing glassy phase network provides new reaction channels, which is beneficial for improving the subsequent decomposition rate of lithium difluorophosphate.

[0051] The decomposition process of lithium difluorophosphate in this application is precisely controlled by the interfacial diffusion kinetics between the positive electrode and the electrolyte membrane: in the intact region, lithium difluorophosphate molecules are tightly wrapped and diffusion is restricted; while in the defect region, the high porosity and electric field gradient drive the molecules to migrate to the high potential region, ensuring that the reaction only occurs at the repair site, thus achieving precise repair of lithium difluorophosphate.

[0052] Both the Li-Al-FO glass phase and the oxyacid salt in this application contain fluorine. The two work together to form a dual fluorine source system. The Li-Al-FO glass layer provides initial rigid protection, blocking electrons and inhibiting the surface oxidation of the positive electrode active material. The oxyacid salt decomposes and fills defects at the interface between the positive electrode and the electrolyte, forming secondary protection. The two work together to construct a fluorine-rich positive electrode electrolyte membrane (CEI), achieving a balance between high voltage stability and low interfacial impedance in solid-state batteries.

[0053] In some embodiments, the mass of the oxyacid salt is 0.05 wt% to 0.15 wt% of the mass of the positive electrode active material, specifically 0.05 wt%, 0.08 wt%, 0.10 wt%, 0.12 wt%, 0.15 wt%, or any value within the range of any two of the above values. If the mass of the oxyacid salt is less than 0.05 wt% of the mass of the positive electrode active material, the repair effect of the oxyacid salt is insufficient. If the mass of the oxyacid salt is greater than 0.15 wt% of the mass of the positive electrode active material, the excess oxyacid salt forms a local high-concentration region at the interface between the positive electrode and the electrolyte membrane, leading to uneven accumulation of decomposition products and increased brittleness at the interface between the positive electrode and the electrolyte membrane. Optionally, the amount of oxyacid salt used is 0.08 wt% to 0.12 wt% of the mass of the positive electrode active material.

[0054] In some implementations, the solid-state battery is a solid-state battery after formation, in which a fluorine concentration gradient is formed between the composite cathode material layer and the electrolyte membrane. The concentration of fluorine decreases from the electrolyte membrane side to the cathode active material side, which effectively blocks electron leakage and ensures rapid lithium-ion transport, achieving the best balance between protection performance and electrochemical performance.

[0055] Before solid-state battery formation, no gradient structure is formed; only the Li-Al-FO glass phase and oxyacid salts are independently distributed. After solid-state battery formation, oxyacid salts preferentially decompose at the interface between the composite cathode material layer and the electrolyte membrane. Their decomposition products mainly deposit at defects in the Li-Al-FO glass phase and in the highly active contact region between the Li-Al-FO glass phase and the cathode active material. Because these decomposition products only fill specific local areas, while other areas retain the original glass phase structure, it is beneficial to form a structure where the component concentration changes gradually with depth: Outermost layer (contact with the cathode active material): Al and O element concentrations are highest (from the original glass phase), and F element has a certain concentration. Middle region: Al concentration gradually decreases, P and F concentrations slowly increase (decomposition products LiF and BOF-containing glassy substances begin to appear). Innermost layer (closest to the electrolyte membrane): P and F concentrations significantly increase (decomposition products LiF and BOF-containing glassy substances are enriched), and Al concentration is lowest. This interface composition and elemental distribution can be characterized and confirmed using surface / cross-sectional elemental analysis methods.

[0056] This application also provides a method for preparing the above-mentioned solid-state battery. Figure 3 A schematic diagram of a solid-state battery fabrication process is shown, such as... Figure 3 As shown, it includes the following steps: A positive electrode active material was obtained, and the positive electrode active material was coated with Li-Al-FO glass phase precursor solution to obtain the first precursor. An ion conductor is obtained by mixing the first precursor and the ion conductor and then performing a molding process to obtain a composite cathode material layer. A solution containing oxyacid salts is coated onto the surface of a composite cathode material layer and then dried to form a cathode; or An electrolyte membrane body is obtained by coating a solution including an oxoacid salt onto the surface of the electrolyte membrane body and drying it to form an electrolyte membrane; wherein the oxoacid salt contains fluorine and lithium elements; A negative electrode is obtained, and the positive electrode, electrolyte membrane and negative electrode are stacked to form an electrode assembly, which is then formed to obtain a solid-state battery.

[0057] In the above scheme, using a Li-Al-FO glass phase precursor solution to coat the positive electrode active material helps reduce grain boundaries and defects on the surface of the positive electrode active material, improving its interfacial stability. Furthermore, the Li-Al-FO glass phase possesses certain ion conductivity, enhancing lithium-ion transport efficiency. Coating the surface of the composite positive electrode material layer with a solution containing oxyacid salts (containing fluorine and lithium) preferentially decomposes compared to the Li-Al-FO glass phase during the charge-discharge process of the solid-state battery. This in-situ decomposition forms LiF and oxyfluorides, which can fill pinholes and cracks in the Li-Al-FO glass phase, further improving the interfacial stability of the positive electrode active material. In this application, the Li-Al-FO glass phase and the oxyacid salts containing fluorine and lithium can form a dual fluorine source between the positive electrode and the electrolyte membrane, achieving a synergistic effect of static protection and dynamic repair, significantly improving the long-term stability of the interface between the positive electrode and the electrolyte membrane.

[0058] The preparation method of the solid-state battery in this application is described in detail below: S100. Obtain the positive electrode active material. Coat the positive electrode active material with Li-Al-FO glass phase precursor solution to obtain the first precursor.

[0059] In some embodiments, a method for preparing the Li-Al-FO glass phase precursor is as follows: a. Obtain AlF3 sol and LiF dispersion.

[0060] In some embodiments, AlF3 sol is prepared by a non-aqueous sol-gel method (e.g., the fluorination reaction of aluminum isopropoxide with anhydrous hydrogen fluoride, which generates Al-F bonds and releases the corresponding alcohol, thereby directly forming AlF3 sol), or it can be purchased directly through commercial channels, which is not limited herein.

[0061] In some embodiments, the concentration of the AlF3 sol is 0.03 mol / L to 0.06 mol / L. The solvent in the AlF3 sol includes at least one of ethanol and water; optionally, the solvent includes ethanol and water in a volume ratio of 9:1. It should be noted that the concentration of the AlF3 sol from 0.03 mol / L to 0.06 mol / L means that each liter of AlF3 sol contains 0.03 mol to 0.06 mol of AlF3 solute.

[0062] In some embodiments, the LiF dispersion is obtained by the following steps: in an inert atmosphere glove box, high-purity LiF with a purity of ≥99.99% is dispersed in a mixed solvent of anhydrous ethanol and ultrapure water with a volume ratio of (5~7):(3~5), and ball milling or ultrasonic treatment is used to fully disperse the LiF. Finally, the LiF dispersion is obtained by centrifugation and filtration.

[0063] b. Under stirring conditions, AlF3 sol and LiF dispersion are ball-milled or ultrasonically treated to obtain Li-Al-FO glass phase precursor solution.

[0064] AlF3 sol does not completely dissolve in an ethanol / water mixture; instead, it forms a mixture of [AlF6] sol and [AlF6]. 3- In a colloidal system where coordination units are complexed with water molecules, some AlF3 hydrolyzes to form aluminum hydroxy fluoride. LiF nanoparticles are broken down by ultrasonic / ball milling, and the surface lattice is disrupted by mechanical shearing, exposing highly active F. - Site. When the two are mixed, the local high pressure and high frequency vibration generated by ball milling / ultrasound promote Li + With [AlF6] 3- Dynamic ion exchange occurs, and oxygen atoms in the solvent combine to form a Li-Al-FO glass phase precursor solution.

[0065] In some embodiments, the general chemical formula of the Li-Al-FO glass phase in the Li-Al-FO glass phase precursor solution is LiAlF. 4-a O a , 0 < a ≤ 0.3.

[0066] In some embodiments, another method for preparing the Li-Al-FO glass phase precursor is as follows: AlF3 sol and lithium trifluoroacetate solution were obtained, and the AlF3 sol and lithium trifluoroacetate solution were aged to obtain Li-Al-FO glass phase precursor solution.

[0067] In some embodiments, the lithium trifluoroacetate solution is obtained by dissolving lithium trifluoroacetate in ethanol to obtain a lithium trifluoroacetate solution with a concentration of 0.03 mol / L to 0.06 mol / L.

[0068] In some embodiments, the aging treatment temperature is 240°C to 260°C, and the aging treatment time is 12h to 24h. By controlling the temperature and time of the aging treatment, the intermolecular interaction between AlF3 sol and lithium trifluoroacetate is promoted, and oxygen atoms in the solvent are combined to form a Li-Al-FO glass phase precursor solution.

[0069] In some embodiments, the general chemical formula of the Li-Al-FO glass phase in the Li-Al-FO glass phase precursor solution is LiAlF. 4-a O a , 0 < a ≤ 0.3.

[0070] In some embodiments, the coating treatment of the positive electrode active material with Li-Al-FO glass phase precursor solution includes the following steps: spray drying the surface of the positive electrode active material with Li-Al-FO glass phase precursor solution at a temperature of 100℃~150℃ for 20min~40min, controlling the increase in solid content of the positive electrode active material after spray drying to be 0.2wt%~1wt%; and heat-treating the spray-dried material in a nitrogen or argon atmosphere at a temperature of 3℃ / min~10℃ / min to 240℃~260℃ for 20min~40min to obtain the first precursor.

[0071] The heat treatment temperature in this application is 240℃~260℃, specifically 240℃, 243℃, 245℃, 248℃, 250℃, 252℃, 255℃, 258℃, 260℃, or any value within the range of any two of the above values. Controlling the heat treatment temperature within this range allows AlF3 and LiF or lithium trifluoroacetate in the Li-Al-FO glass phase precursor solution to interact, forming a Li-Al-FO network structure with a stoichiometry close to LiAlF4, i.e., the glass phase, while simultaneously avoiding phase transitions and decomposition of the positive electrode active material.

[0072] S200. Obtain the ion conductor. Mix the first precursor and the ion conductor and then perform molding to obtain the composite cathode material layer.

[0073] Specifically, the process includes the following steps: a first precursor, an ionic conductor, a conductive agent (such as carbon nanotubes or supercarbon), and a binder powder (such as polytetrafluoroethylene) are added to a high-speed mixing device at a predetermined mass ratio for dry mixing, followed by hot pressing to obtain a composite cathode material layer. Alternatively, this application can also use a wet mixing method to mix the first precursor, ionic conductor, conductive agent, and binder; this application does not impose any limitations on this method.

[0074] In some embodiments, the mass ratio of the first precursor, ionic conductor, conductive agent and binder is (50~80):(20~40):(1~10):(1~5), specifically it can be 50:35:10:5, 60:35:3:2, 70:20:9:1, 80:12:5:3 or any value within the range of any two of the above values.

[0075] In some embodiments, the conductive agent includes, but is not limited to, carbon nanotubes and vapor-grown carbon fibers.

[0076] In some embodiments, the binder powder includes, but is not limited to, polytetrafluoroethylene.

[0077] In some embodiments, the hot pressing temperature is 20°C to 80°C and the pressure is 15MPa to 20MPa.

[0078] S300: A solution including an oxyacid salt is coated onto the surface of a composite cathode material layer and dried to form a cathode; or an electrolyte membrane body is obtained by coating a solution including an oxyacid salt onto the surface of the electrolyte membrane body and drying to form an electrolyte membrane, wherein the oxyacid salt contains fluorine and lithium.

[0079] In some embodiments, the solution comprising the oxoacid salt is prepared by dissolving the oxoacid salt in a fluorinated ether solvent to prepare a solution with a concentration of 1.0 wt%. The fluorinated ether solvent includes HFE-7100 or HFE-7300.

[0080] In some embodiments, the mass of the oxoacid in the solution of the oxoacid is 0.05wt% to 0.15wt% of the mass of the positive electrode active material, specifically it can be 0.05wt%, 0.08wt%, 0.1wt%, 0.12wt%, 0.15wt%, or any value within the range of any two of the above values.

[0081] In some embodiments, the coating method includes spraying, which can precisely introduce oxyacid salts into the contact interface between the cathode material layer and the electrolyte membrane.

[0082] S400: Obtain the negative electrode, stack the positive electrode, electrolyte membrane and negative electrode to form an electrode assembly, and obtain a solid-state battery after formation.

[0083] Specifically: In a glove box, the positive electrode, electrolyte membrane, and negative electrode are stacked sequentially, and an initial pressure of 10 MPa is applied. Then, the mixture is transferred to a mold, where a working pressure of 5 MPa to 20 MPa is applied. The initial charge-discharge cycle uses a small current of 0.1C to 0.2C to activate the decomposition of oxyacid salts and the formation of CEI. Optionally, constant voltage-limited pre-activation is performed at 4.6-4.8V to gently trigger the initial cleavage and pinhole repair of oxyacid salts. The first 2-3 cycles constitute the formation stage, during which the CEI is gradually optimized and stabilized.

[0084] This application also provides another method for preparing the above-mentioned solid-state battery. Figure 4 A schematic diagram of a solid-state battery fabrication process is shown, such as... Figure 4 As shown, it includes the following steps: A positive electrode active material and an ion conductor are obtained. The positive electrode active material and the ion conductor are mixed and then subjected to molding treatment to obtain a composite positive electrode material layer. The Li-Al-FO glass phase precursor solution was coated on the surface of the composite cathode material and dried to form the first interface layer. A solution comprising an oxyacid salt is coated onto the surface of a first interface layer, and after drying, a second interface layer is formed to obtain a second precursor; wherein the oxyacid salt contains fluorine and lithium elements; An electrolyte membrane and a negative electrode are obtained. The second precursor, the electrolyte membrane, and the negative electrode are stacked to form an electrode assembly, which is then formed to obtain a solid-state battery.

[0085] In the above scheme, a Li-Al-FO glass phase precursor solution is coated on the surface of the composite cathode material and dried to form a first interface layer. The first interface layer includes the Li-Al-FO glass phase. A solution including an oxyacid salt is coated on the surface of the first interface layer and dried to form a second interface layer. The second interface layer includes an oxyacid salt containing fluorine and lithium. The Li-Al-FO glass phase and the oxyacid salt containing fluorine and lithium can form a dual fluorine source between the cathode and the electrolyte membrane, achieving a synergistic effect of static protection and dynamic repair, and significantly improving the long-term stability of the cathode and electrolyte membrane interface.

[0086] The difference between this embodiment and the solid-state battery described above is that a solution including an oxyacid salt is coated onto the surface of the first interface layer, and after drying, a second interface layer is formed. The coating method can be, for example, spin coating.

[0087] In some embodiments, the mass of the oxyacid in the oxyacid solution is 0.05wt% to 0.15wt% of the mass of the positive electrode active material, specifically 0.05wt%, 0.08wt%, 0.1wt%, 0.12wt%, 0.15wt%, or any value within the range of any two of the above values. Controlling the mass of the oxyacid in the oxyacid solution to be within the above range allows for a thinner second interface layer while simultaneously achieving a dynamic repair effect of the oxyacid on the first interface layer.

[0088] This application provides a battery device including the solid-state battery described above. This battery device can be used, but is not limited to, in electrical devices or energy storage devices such as vehicles, ships, or aircraft. A power system for an electrical device or energy storage device can be formed using the battery device disclosed in this application, improving the stability of battery performance and battery life.

[0089] This application provides an electrical device that uses a battery as a power source. The electrical device includes, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.

[0090] This application also provides an energy storage device that uses a battery as a power source. The energy storage device includes, but is not limited to, energy storage containers, energy storage cabinets, energy storage power stations, energy storage battery packs, or portable energy storage systems.

[0091] The embodiments of this application will be further described below with reference to several examples. However, the embodiments of this application are not limited to the specific embodiments described below. Appropriate modifications can be made without departing from the scope of the claims.

[0092] Example 1: (1) Preparation of Li-Al-FO glass phase precursor solution: AlF3 sol (concentration of 0.04 mol / L) and high-purity LiF nano-dispersion (a mixed solvent of ethanol and water with a volume ratio of 7:3, with LiF particle size less than 100 nm by ball milling) were mixed at an Al:F atomic ratio of 1:3.98 and ultrasonically stirred for 2 h to obtain Li-Al-FO glass phase precursor solution.

[0093] The Li-Al-FO glass phase precursor solution should be stored in a sealed container and filtered through a 0.22 μm filter membrane to remove particulate impurities before use. (2) Prepare a solution containing oxyacid salts: Lithium difluorophosphate was dispersed in HFE-7100 solvent to prepare a 1.0 wt% solution of the oxyacid salt. The solution should be freshly prepared before use to avoid decomposition due to long-term storage.

[0094] (3) Commercial high-voltage spinel-type LNMO powder (LiNi) 0.5 Mn 1.5 O4 (particle size D50 = 55 μm ~ 8 μm, specific surface area 1.2 m2 / g) was dried in a vacuum oven at 120°C for 4 h to make the residual moisture <100 ppm; the Li-Al-FO glass phase precursor liquid obtained in step (1) was sprayed onto the surface of LNMO powder using an ultrasonic atomization spraying system with an atomization frequency of 1.7 MHz, a carrier gas (N2) flow rate of 1 L / min, a spraying rate of 0.5 mL / min, and a solid content weight gain of 0.3 wt%. It was dried at 120°C for 30 min, and after removing the solvent, it was transferred to a tube furnace and heated to 250°C at 5°C / min under argon protection and held for 30 min to form a Li-Al-FO glass phase coating layer on the surface of LNMO powder. Then, by slowly cooling (cooling rate less than 5°C / min), the thermal stress caused by the coating layer cracking was avoided. The residual moisture was determined by Karl Fischer method to be ≤45 ppm, and the first precursor was obtained. The thickness of the Li-Al-FO glass phase coating is 7 nm.

[0095] After heat treatment, the residual moisture content of the material must be ≤50ppm (determined by Karl Fischer method) before it can come into contact with the halide solid electrolyte.

[0096] (4) The first precursor is mixed with Li3YCl6 (particle size 3μm), conductive carbon and polytetrafluoroethylene in a mass ratio of 60:35:3:2 and cold-pressed at 300MPa to form a composite cathode material layer.

[0097] (5) Spray the solution of the oxyacid salt obtained in step (2) onto the surface of the composite cathode material layer, control the solid content weight gain to 0.1 wt%, vacuum dry at 60°C for 10 min, remove the solvent, and obtain the cathode.

[0098] (6) Assemble the positive electrode, Li3YCl6 electrolyte membrane and Li-In metal negative electrode obtained in step (5) into a solid-state battery.

[0099] XPS analysis of the solid-state battery presented in this application revealed Al-2p, F-1s (expected to be a dual-component structure of Li-F and Al-F), and P-2p (PF / POF component) signals at the cathode / electrolyte interface after formation. Prior to formation, only the Al-F component was expected; the addition of PF and Li-F components after formation indicates the decomposition of lithium difluorophosphate and the evolution of the electrolyte interface film.

[0100] When the solid-state battery of this application was subjected to ToF-SIMS detection, along the direction from the electrolyte membrane to LNMO, it was found that Al and F signals were enriched in the near-surface layer, PF and OP species signals were enhanced in the subsurface layer, and LNMO signals reverted in the deeper layers, which confirmed that the concentration of fluorine decreased from the electrolyte membrane side to the positive electrode active material side.

[0101] Example 2 Unlike Example 1, (1) Preparation of Li-Al-FO glass phase precursor solution: AlF3 sol (concentration of 0.04mol / L) and lithium trifluoroacetate ethanol solution (concentration of 0.04mol / L) were mixed at an Al:F atomic ratio of 1:4 and aged at 250℃ for 18h to obtain Li-Al-FO glass phase precursor solution.

[0102] Example 3 Unlike Example 1, (3) Commercial high-voltage spinel-type LNMO powder (particle size D50 = 5 μm ~ 8 μm, specific surface area 1.2 m2 / g) was dried in a vacuum oven at 120°C for 4 h to reduce residual moisture to <100 ppm. The LNMO powder was mixed with Li3YCl6 (particle size 3 μm), conductive carbon and polytetrafluoroethylene in a mass ratio of 60:35:3:2 and cold-pressed at 300 MPa to form a composite cathode material layer.

[0103] (4) The Li-Al-FO glass phase precursor solution was uniformly spin-coated (3000 rpm, 30 s) onto the surface of the composite cathode material layer to form a uniform liquid film. After drying at 120°C for 30 min to remove the solvent, it was transferred to a tube furnace and heated to 230°C at 5°C / min under argon protection and held for 90 min to form a Li-Al-FO glass phase coating layer on the surface of LNMO powder. Then, the temperature was slowly lowered (cooling rate less than 5°C / min) to avoid thermal stress causing cracking of the coating layer. The residual moisture content was determined by Karl Fischer method to be ≤45 ppm, thus obtaining the first precursor. The thickness of the Li-Al-FO glass phase coating layer was 7 nm.

[0104] Example 4 Unlike Example 1, in (1), AlF3 sol and high-purity LiF nano-dispersion were mixed at an Al:F atomic ratio of 1:3.9.

[0105] Example 5 Unlike Example 1, in (1), AlF3 sol and high-purity LiF nano-dispersion were mixed at an Al:F atomic ratio of 1:3.8.

[0106] Example 6 Unlike Example 1, in (1) AlF3 sol and high-purity LiF nano-dispersion were mixed at an Al:F atomic ratio of 1:3.7.

[0107] Example 7 Unlike Example 1, in (2), lithium difluorophosphate is replaced with lithium difluorooxalate borate.

[0108] Example 8 Unlike Example 1, in (3), the spraying rate was 0.5 mL / min, the solid content weight gain was 0.16 wt%, and the thickness of the Li-Al-FO glass phase coating was 4 nm.

[0109] Example 9 Unlike Example 1, in (3), the spraying rate was 0.5 mL / min, the solid content weight gain was 0.2 wt%, and the thickness of the Li-Al-FO glass phase coating was 5 nm.

[0110] Example 10 Unlike Example 1, in (3), the spraying rate was 0.5 mL / min, the solid content weight gain was 0.5 wt%, and the thickness of the Li-Al-FO glass phase coating was 10 nm.

[0111] Example 11 Unlike Example 1, in (3), the spraying rate was 0.5 mL / min, the solid content weight gain was 0.55 wt%, and the thickness of the Li-Al-FO glass phase coating was 12 nm.

[0112] Example 12 Unlike Example 1, the solid content in (5) increased by 0.03 wt%.

[0113] Example 13 Unlike Example 1, the solid content in (5) increased by 0.05 wt%.

[0114] Example 14 Unlike Example 1, the solid content in (5) increased by 0.15 wt%.

[0115] Example 15 Unlike Example 1, the solid content in (5) increased by 0.18 wt%.

[0116] Example 16 Unlike Example 1, in (3), before spraying the Li-Al-FO glass phase precursor liquid obtained in step (1) onto the surface of LNMO powder, the following steps are also included: spraying the LNMO powder surface with an ethanol solution of lithium nitrate and an ethanol solution of niobium ethanol (0.01 mol / L each), and treating it at 200°C for 30 min to form an ultrathin bonding layer of 2 nm.

[0117] After an ultrathin bonding layer is formed on the surface of LNMO powder, it should be stored in a dry environment (dew point < -40℃) or an inert atmosphere glove box to avoid reabsorption of water.

[0118] Example 17 Unlike Example 1, in (3) and (6), Li3InCl6 is used instead of Li3YCl6.

[0119] Comparative Example 1 Unlike Example 1, steps (1) and (2) are omitted. Commercial high-voltage spinel-type LNMO powder, Li3YCl6 (particle size 3μm), conductive carbon and polytetrafluoroethylene are directly mixed in a mass ratio of 60:35:3:2 and cold-pressed at 300MPa to form a composite cathode material layer to obtain the cathode. The cathode, Li3YCl6 electrolyte membrane and Li metal anode are then assembled into a solid-state battery.

[0120] Comparative Example 2 Unlike Example 3, step (1) is omitted.

[0121] Comparative Example 3 Unlike Example 1, steps (1) and (3) are not performed.

[0122] Comparative Example 4 Unlike Example 1, step (1) is omitted; instead, commercial high-voltage spinel-type LNMO powder (LiNi) is coated with crystalline AlF3. 0.5 Mn 1.5 O4, particle size D50 = 55μm~8μm, specific surface area 1.2m² 2 / g).

[0123] Comparative Example 5 Unlike Example 1, step (5) is omitted. Instead, the solution of the oxyacid salt obtained in step (2) is dried and then added to step (4).

[0124] The performance of the products prepared in the above examples and comparative examples was measured, and the results are shown in Table 1.

[0125] Table 1. Comparison of Examples and Comparative Cases

[0126] The solid-state battery of this application achieves the following technical effects: This application constructs a composite interface consisting of a Li-Al-FO glass phase coating and oxyacid salts containing fluorine and lithium. The Li-Al-FO glass phase coating serves as the initial protective layer, while the oxyacid salts containing fluorine and lithium decompose in situ at interface defects to generate LiF, thus achieving a synergistic effect of static protection and dynamic repair. This invention, through the synergistic effect of the Li-Al-FO glass phase and the oxyacid salts containing fluorine and lithium, solves the problems of traditional single-fluorine source coatings failing to simultaneously provide initial protection and dynamic repair, as well as the insufficient interface stability caused by uneven distribution of additives in solid-state battery systems.

[0127] The Li-Al-FO glass phase of this application has an amorphous structure, is free of grain boundary defects, maintains continuous coverage at a relatively thin thickness, and has an ionic conductivity ranging from 10. -7 S / cm~10 -6 The S / cm conductivity is significantly better than that of crystalline fluorides (typically 10). -9 S / cm ~10 -10 The Li-Al-FO glass phase (S / cm) solves the problems of poor interface continuity and low ionic conductivity caused by island growth in traditional crystalline fluorides at ultrathin thicknesses. Furthermore, the dense structure of the Li-Al-FO glass phase can block halogen migration and is suitable for strong oxidizing environments. This application provides redundancy protection through the Li-Al-FO glass phase and oxoacid salts containing lithium and fluorine elements to ensure high voltage stability.

[0128] This application adds a certain amount of oxyacid salt, which can be precisely applied to the interface between the positive electrode and the electrolyte. The position and concentration are controlled by the spraying process to ensure that it only plays a role in the interface area and does not affect the bulk performance of the electrolyte. This solves the problems of low utilization and side reaction risk caused by traditional bulk addition.

[0129] Compared to Examples 1-18, in Comparative Example 1, the high-voltage spinel-type LNMO comes into direct contact with the halide electrolyte, resulting in severe oxidative decomposition at a working voltage of 4.7V. This leads to a surge in interfacial impedance and a significant decrease in ionic conductivity, resulting in a significant deterioration in the rate performance and cycle performance of the solid-state battery. Simultaneously, severe Mn dissolution and oxygen release cause the cathode structure to continuously collapse, leading to a rapid decline in battery performance.

[0130] Compared to Examples 1-18, Comparative Example 2 only had a Li-Al-FO glass phase without introducing fluorinated lithium salt. During long-term cycling, the interfacial impedance rebounded significantly and the cycling capacity retention rate was lower than that of the examples with dynamic repair by fluorinated lithium salt. This indicates that the dynamic repair effect of fluorinated lithium salt in the dual-fluorine source is indispensable for the long-term stability of the interface.

[0131] Compared to Examples 1-18, Comparative Example 3 only introduced fluorinated lithium salt without providing a Li-Al-FO glass layer. Although the fluorinated lithium salt can form a film in situ to provide protection, the lack of a fluid medium in the solid-state battery system makes it difficult for the fluorinated lithium salt to achieve uniform diffusion and distribution at the interface, which can easily lead to local side reactions or increased impedance. Moreover, in the early stages of battery cycling, the fluorinated lithium salt has not yet decomposed or has not decomposed sufficiently, and therefore cannot provide effective protection.

[0132] Compared to Examples 1-18, Comparative Example 4 uses crystalline AlF3 instead of the Li-Al-FO glass phase. Crystalline AlF3 cannot form a continuous film under ultrathin thickness conditions, resulting in a sharp increase in interfacial impedance. Furthermore, the poor ionic conductivity of crystalline AlF3 cannot meet the requirements for high-rate performance.

[0133] Compared to Examples 1-18, Comparative Example 5, which incorporates fluorinated lithium salt into the composite cathode material layer, has low utilization of the fluorinated lithium salt and may trigger side reactions, resulting in insufficient performance improvement of the solid-state battery.

[0134] The above description is only a preferred embodiment of this application, but this application does not limit the scope of implementation to what is shown in the drawings. Any changes made in accordance with the concept of this application, or equivalent embodiments modified to have equivalent changes, shall still be within the scope of protection of this application if they do not exceed the spirit covered by the specification and drawings.

Claims

1. A solid-state battery, characterized in that, The solid-state battery includes a positive electrode, a negative electrode, and an electrolyte membrane, wherein the electrolyte membrane is located between the positive electrode and the negative electrode, and the positive electrode includes a composite positive electrode material layer, wherein the composite positive electrode material layer includes a positive electrode active material and an ion conductor; The positive electrode further includes a coating layer located on the surface of the positive electrode active material, the coating layer comprising a Li-Al-FO glass phase, the general chemical formula of which is LiAlF. 4-a O a , 0 < a ≤ 0.3; An oxyacid salt is further disposed between the composite cathode material layer and the electrolyte membrane. The oxyacid salt includes at least one of lithium difluorophosphate and lithium difluorooxalate borate, and the mass of the oxyacid salt is 0.05wt% to 0.15wt% of the mass of the cathode active material.

2. A solid-state battery, characterized in that, The solid-state battery includes a positive electrode, a negative electrode, and an electrolyte membrane, wherein the electrolyte membrane is located between the positive electrode and the negative electrode, and the positive electrode includes a composite positive electrode material layer, wherein the composite positive electrode material layer includes a positive electrode active material and an ion conductor; The positive electrode further includes an interface layer located between the composite positive electrode material layer and the electrolyte membrane. The interface layer includes a first interface layer and a second interface layer. The second interface layer is located between the first interface layer and the electrolyte membrane. The first interface layer includes a Li-Al-FO glass phase with the general chemical formula LiAlF. 4- a O a 0 < a ≤ 0.3, the second interface layer includes an oxyacid salt, the oxyacid salt including at least one of lithium difluorophosphate and lithium difluorooxalate borate, the mass of the oxyacid salt being 0.05 wt% to 0.15 wt% of the mass of the positive electrode active material.

3. The solid-state battery according to claim 1 or 2, characterized in that, The electronic conductivity of the Li-Al-FO glass phase is less than or equal to 10. -12 S / cm; The Li-Al-FO glass phase has an ionic conductivity of 10 at room temperature. -7 S / cm~10 -6 S / cm.

4. The solid-state battery according to claim 1 or 2, characterized in that, The solid-state battery is a solid-state battery after formation. A concentration gradient of fluorine is formed between the composite cathode material layer and the electrolyte membrane. The concentration of fluorine decreases from the electrolyte membrane side to the composite cathode material layer side.

5. The solid-state battery according to claim 1 or 2, characterized in that, The positive electrode active material includes lithium nickel manganese oxide and its derivatives; The electrolyte membrane includes a first halide with the general chemical formula Li3MCl6, where M includes at least one of Y, In, Sc, Er and Yb. The ionic conductor includes a second halide with the general chemical formula Li3MCl6, where M includes at least one of Y, In, Sc, Er, and Yb.

6. The solid-state battery according to claim 1, characterized in that, The thickness of the coating layer is 5nm~50nm.

7. The solid-state battery according to claim 1, characterized in that, A connecting layer is also provided between the positive electrode active material and the coating layer; The connecting layer includes at least one of LiNbO3, Li3PO4, Al2O3, TiO2, and La2O3; The thickness of the connecting layer is 1nm to 3nm.

8. The solid-state battery according to claim 2, characterized in that, The thickness of the first interface layer is 5nm~50nm.

9. A method for preparing a solid-state battery, characterized in that, Includes the following steps: A positive electrode active material was obtained by coating it with a Li-Al-FO glass phase precursor solution to obtain a first precursor. The general chemical formula of the Li-Al-FO glass phase in the Li-Al-FO glass phase precursor solution is LiAlF. 4- a O a , 0 < a ≤ 0.3; An ion conductor is obtained by mixing the first precursor and the ion conductor and then performing a molding process to obtain a composite cathode material layer. A solution containing oxyacid salts is coated onto the surface of the composite cathode material layer and then dried to form a cathode; or To obtain an electrolyte membrane body, a solution including an oxyacid salt is coated onto the surface of the electrolyte membrane body and dried to form an electrolyte membrane. The oxyacid salt includes at least one of lithium difluorophosphate and lithium difluorooxalate borate, and the mass of the oxyacid salt is 0.05wt% to 0.15wt% of the mass of the positive electrode active material. A negative electrode is obtained, and the positive electrode, the electrolyte membrane, and the negative electrode are stacked to form an electrode assembly, which is then formed to obtain a solid-state battery.

10. A method for preparing a solid-state battery, characterized in that, Includes the following steps: A positive electrode active material and an ion conductor are obtained. The positive electrode active material and the ion conductor are mixed and then subjected to molding treatment to obtain a composite positive electrode material layer. A Li-Al-FO glass phase precursor solution is coated onto the surface of the composite cathode material layer, and after drying, a first interface layer is formed. The general chemical formula of the Li-Al-FO glass phase in the Li-Al-FO glass phase precursor solution is LiAlF. 4-a O a , 0 < a ≤ 0.3; A solution comprising an oxyacid salt is coated onto the surface of the first interface layer, and after drying, a second interface layer is formed to obtain a second precursor; wherein the oxyacid salt comprises at least one of lithium difluorophosphate and lithium difluorooxalate borate, and the mass of the oxyacid salt is 0.05wt%~0.15wt% of the mass of the positive electrode active material; An electrolyte membrane and a negative electrode are obtained. The second precursor, the electrolyte membrane, and the negative electrode are stacked to form an electrode assembly, which is then formed to obtain a solid-state battery.

11. The preparation method according to claim 9 or 10, characterized in that, The Li-Al-FO glass phase precursor solution was prepared using the following steps: AlF3 sol and LiF dispersion were obtained. Under stirring conditions, the AlF3 sol and LiF dispersion were subjected to ball milling or ultrasonic treatment to obtain Li-Al-FO glass phase precursor solution.

12. The preparation method according to claim 9 or 10, characterized in that, The Li-Al-FO glass phase precursor solution was prepared using the following steps: AlF3 sol and lithium trifluoroacetate solution were obtained, and the AlF3 sol and lithium trifluoroacetate solution were subjected to aging treatment to obtain Li-Al-FO glass phase precursor solution.

13. A battery device, characterized in that, The solid-state battery includes a solid-state battery prepared by a method according to any one of claims 1 to 8 or any one of claims 9 to 12, wherein the battery device includes one or more of a battery module, a battery pack, and an energy storage battery.

14. An electrical appliance, characterized in that, The electrical device includes the battery device of claim 13, the battery device being used to obtain electrical energy.

15. An energy storage device, characterized in that, The energy storage device includes the battery device of claim 13, the battery device being used to store electrical energy.

Citation Information

Patent Citations

  • Lithium ion battery

    CN121885729A

  • Solid-state battery and preparation method thereof, battery device, power utilization device and energy storage device

    CN122051322A